Pendampingan Pemanfaatan Limbah Kain dalam Peningkatan Ekonomi Masyarakat Nagari Sungai Abang Lubuk Alung - Sunreni, Sunreni; Salfadri, Salfadri; Haryati , Rice; Yanti , Novi; Yulistia, Yulistia; Bakkareng, Bakkareng; Chandrayanti , Teti; Begawati, Nova; M, Agussalim (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2024)
The purpose of this carrying out community service through this mentoring activity is to increase the skills and knowledge of the Salimah women farming group in Sungai Abang village in making creative and innovative products from fabric waste. The methods applied are lectures, discussions and demonstrations. The results of this community service can improve and increase the knowledge and skills of the members of the Salimah women's farmer group in running and developing a fabric waste craft business in the form of chair cushions and seat mats which can have an impact on improving the household economy of the community of Sungai Abang, Lubuk Alung Padang Pariaman, which is part of the community. in the Salimah women's farming group